Low-effort determination of heat capacity and thermal conductivity for cylindrical 18650 and 21700 lithium-ion cells. (October 2021) - Steinhardt, Marco; Gillich, Elisabeth Irene; Rheinfeld, Alexander; Kraft, Ludwig; Spielbauer, Markus; Bohlen, Oliver; Jossen, Andreas
Abstract: High-fidelity simulations of lithium-ion cells describing fast charging or safety-critical events often rely on precise thermal parameters. Usually, the determination of cell parameters such as heat capacity or thermal conductivity is time consuming and cost intensive. To streamline this process, a simple yet precise measurement method for determining the specific heat capacity of lithium-ion cells is now extended by an approach that also captures their thermal conductivity. The method presented here was developed using two cylindrical cell formats, each containing a lithium–nickel–manganese–cobalt-oxide (NMC) cathode and a silicon-graphite anode. The extension is based on a two-dimensional finite element (FEM) model, whose geometry is parameterized by computed tomography (CT) scans. To ensure the simplicity of the experimental evaluation, the FEM model is approximated by a rational function. The new measurement method is applied at three different temperatures and states of charge (SOC). The results show that while the specific heat capacity of the jelly roll increases with temperature by 0.2%/K for both cell formats, it is only minimally influenced by the SOC. In contrast, the through-plane thermal conductivity of the electrode-separator-composite decreases by -0.5%/K and is enhanced by up to 9% by increasing the SOC in a window ranging from 10% to 71%.